Alternatives in agriculture - ideology or utopia? - Peuker, Birgit (Momentum Quarterly, 2014)
The article traces the concept of family-based agriculture as ideology in hundred years (1870-1970) of agricultural development in Germany. Agricultural interest groups and agricultural policy were ideological seeking to preserve small-scale family-farming meanwhile structural changes in agriculture took place. Three aspects of ideology – simplification, generalization and symbolic reference to reality – are identified in the first section with recourse to Karl Mannheim and an example given by C. Wright Mills. An overview of agricultural politics and history shows a fourth aspect of agricultural ideology in Germany: the convergence of ideology and utopia, due to merging interests of small-scale farmers and large-scale farmers in agricultural interest groups.
Keywords: family-based agriculture; ideology; industrialized agriculture; agricultural policy